How successful is SOX in promoting corporate accountability: Evidence from listed companies in the United States of America and the Philippines from 2004 to 2012 - Hui, Christine C. (Animo Repository, 2020)
This study aims to evaluate how successful was the Sarbanes-Oxley Act in promoting corporate accountability from 2004 to 2012 by examining whether it has prevented fraudulent financial reporting through empirical research based on the United States Securities and Exchange Commission’s Accounting and Auditing Enforcement Releases, annual reports and proxy statements of selected listed companies in the United States and listed companies in the Philippines affiliated with listed companies in the United States. This study looked into the effect of the enactment of the Sarbanes-Oxley Act, management’s assessment of internal control effectiveness, auditor’s attestation on management’s assessment of internal control effectiveness, independence of audit committee members and presence of audit committee member with financial expertise on fraud through the use of logistic regression models. Furthermore, the relationship between fraud and the said variables have been examined. The results of this study, which covered 345 listed companies in the United States and listed companies in the Philippines affiliated with listed companies in the United States for the fiscal years ending 1999 to 2012, suggest that the Sarbanes-Oxley Act was not as effective in deterring fraudulent financial reporting. Moreover, the enactment of the Sarbanes-Oxley Act, management’s assessment of internal control effectiveness, auditor’s attestation on the said assessment, independence of audit committee members and presence of an audit committee member with financial expertise are found to be not correlated with fraud.